Coastal Vulnerability Study Dumai City Riau Province - Oktaviani, Vivi; Mulyadi, Aras; Mubarak, Mubarak (Jurnal Perikanan dan Kelautan, 2023)
The purpose of this study was to determine the assessment and category of vulnerability level and calculate the parameters that affect coastal vulnerability. The method used is a survey method with direct observation, while the analysis method used is the calculation of CVI, the root of the multiplication of each variable weight. The data required includes primary data by direct observation, and secondary data with data from remote sensing satellites, primary data including coastal geomorphology, land use, tides, and secondary data including DEM (Digital Elevation Mode), coastal slope, shoreline changes, relative water level rise, significant wave height. The results of this study at the observation location obtained 3 categories of vulnerability namely low, high, and very high vulnerability levels found on the Dumai coast. The category of vulnerability in the low class is located in Dumai Barat District in Purnama Village with a value of 4.33-5.00, and the category of vulnerability in the high class is located in Dumai Timur District in Purnama Village grid A2 and A4 at Tanjung Palas grid A12,-A14 with a value of 8.66-10.61, and the category of vulnerability in the very high class is located in Dumai Barat District grid A5-A8, Dumai City District grid A9-A10, and Dumai Timur District in Tanjung Palas Village grid A15 with a value of 12.99-20.00.